(untitled) (International Journal of Engineering and Computer Science, 2017)
The increasing popularity of cloud computing attracted so many organizations to host cloud services. Due to the enormous growth of cloud data centers the users are now able to put their data in any of the cloud data centers. It is difficult for the cloud service provider to choose an appropriate data center based on the user requirements. To ensure reliability cloud service providers uses replicas. It is essential to load balance among the cloud data centers for better performance. We propose a new method for the distribution of data among the cloud data centers based on the Predictor-Distribute Algorithm (PREDA). Index Terms: Multi Cloud, Erasure and Replication, Predictor.